Distinctions in Disclosure: Mandated Informed Consent in Abortion and ART. Issue 2 (June 2015) - Daar, Judith
<x xml:space="preserve">Abstract</x> Enactment of mandated pre‐procedure disclosures in abortion and assisted reproductive technology (ART) services has swelled in recent years. Calls to equally regard these mandates as neutral tools in furtherance of patient protection fail to acknowledge key substantive and structural differences in these reproduction‐affecting mandates. While ART mandates permit physicians to use their medical judgment to protect presumptively vulnerable egg donors and gestational carriers, abortion disclosures impart scientifically suspect messaging aimed at dissuading women from pursuing pregnancy termination. These and other distinctions counsel in favor of regarding and analyzing abortion and ART mandated disclosures as separate and distinguishable informed consent tools.